2020
DOI: 10.3389/fphar.2020.560209
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Early Combination Therapy With Lianhuaqingwen and Arbidol in Moderate and Severe COVID-19 Patients: A Retrospective Cohort Study

Abstract: Objective: Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan City, China, coronavirus disease 2019 (COVID-19) has become a global pandemic. However, no special therapeutic drugs have been identified for COVID-19. The aim of this study was to search for drugs to effectively treat COVID-19. Materials and Methods: We conducted a retrospective cohort study with a total of 162 adult inpatients (≥18 years old) from Ruijin Hospital (Shanghai, China) and Tongji Hospital (Wuhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In the height of SARS-CoV-2 outbreak in China, LHQWC was recommended again for clinical use to treat COVID-19. Subsequent clinical and experimental studies have confirmed the therapeutic benefits of LHWQC [ 35 , 50 ]. Its mode of action was by targeting virus replication and immunological regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the height of SARS-CoV-2 outbreak in China, LHQWC was recommended again for clinical use to treat COVID-19. Subsequent clinical and experimental studies have confirmed the therapeutic benefits of LHWQC [ 35 , 50 ]. Its mode of action was by targeting virus replication and immunological regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 52 , 53 , 54 compared the efficacy of arbidol as a combination therapy with traditional Chinese medicines. The meta‐analysis of improvement rate of chest CT found no greater benefit of arbidol combined with Lianhuaqingwen compared to arbidol alone in the treatment of COVID‐19 patients (RR: 1.27; 95% CI: 0.88–1.85; p = .20; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The meta‐analysis of improvement rate of chest CT found no greater benefit of arbidol combined with Lianhuaqingwen compared to arbidol alone in the treatment of COVID‐19 patients (RR: 1.27; 95% CI: 0.88–1.85; p = .20; Table 2 ). Fang et al 53 found that the simultaneous treatment of arbidol and Lianhuaqingwen was associated with higher improvement in patients with moderate COVID‐19 compared with Lianhuaqingwen alone. There are other studies 52 , 54 that reported the efficacy and safety of Shufeng Jiedu capsule combined with arbidol versus arbidol alone in patients with COVID‐19.…”
Section: Resultsmentioning
confidence: 99%
“…There were six observational studies on umifenovir, among which PCR negative conversion was the primary endpoint in four. In studies that used lopinavir/ritonavir- or Chinese medicine-treated control group, the time to negative conversion was earlier in the favipiravir group; however, there was no significant difference between the groups in studies that did not treat the control group with antiviral drugs [ 97 98 99 100 ]. Clearance of fever and cough were assessed even when clinical endpoints were selected; more meaningful outcome of mortality, progression to severe disease, or hospital discharge was not reported [ 101 102 ].…”
Section: Resultsmentioning
confidence: 99%